2008
DOI: 10.1002/hc.20414
|View full text |Cite
|
Sign up to set email alerts
|

Researches on thiazolobenzodiazepines: Behavior of tetrahydro‐1,5‐benzodiazepinethiones with aromatic α‐haloketones

Abstract: A number of 1‐substituted 4H,5H,6H‐[1,3]thiazolo[3,2‐a][1,5]benzodiazepinium‐11‐bromides and S‐(2‐oxo‐2‐phenyl‐X‐(p)‐ethyl)‐3‐(2‐methyl‐1H‐benzimidazol‐1‐yl) propane (or butane) thioate hydrobromides were obtained by direct reaction of the 5‐acetyl(or formyl, or anilinocarbonyl)‐substituted tetrahydro‐1,5‐benzodiazepine‐2‐thiones with aromatic α‐bromoketones. 2‐[(1‐Acetyl‐2(or 3)‐methyl‐2,3‐dihydro‐1H‐1,5‐benzodiazepin‐4‐yl) sulfanyl]‐1‐phenylethanones as intermediates of the formation of thiazolo [3,2‐a][1,5]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Consequently, the AM1 geometry optimized structures were used as initial coordinates for optimization at the DFT level using the B3LYP functional and the 6‐31G* basis sets using the program product . The vibrational frequencies were computed for optimized intermediate structures and checked to present no imaginary vibrational frequency to ensure that they were local minima points on potential energy profile . The calculation of local reactivity descriptors was implemented according to .…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, the AM1 geometry optimized structures were used as initial coordinates for optimization at the DFT level using the B3LYP functional and the 6‐31G* basis sets using the program product . The vibrational frequencies were computed for optimized intermediate structures and checked to present no imaginary vibrational frequency to ensure that they were local minima points on potential energy profile . The calculation of local reactivity descriptors was implemented according to .…”
Section: Methodsmentioning
confidence: 99%
“…Aromatic electrophilic substitution (Ar-ES) reactions of benzofused electron-rich five-membered heterocycles are among the most thoroughly studied reactions in organic chemistry owing to their wide range of applications in material sciences and medicine. Materials containing substituted electron-rich five-membered heterocycles are successfully applied to the design of novel liquid crystals. , Many experimental works dealing with an attempt to obtain halogenated electron-rich five-membered heterocycles have been extensively developed in this field. , Moreover, the experimental studies have been carried out to clarify the nature of the electrophilic substitution reaction in these heterocycles. It was suggested that electrophilic substitution in the simple five-membered heterocycles furan and thiophene occurs with positional selectivity and via the aromatic σ-complex. More recently Domingo et al rationalized the relative reactivities of five-membered heterocycles in electrophilic aromatic substitution reaction by means of the global nucleophilicity index. Later Gromri et al extended this investigation and has shown that the experimental trends of the relative reactivities and regioselectivities of these reactions can be correctly predicted using calculated global nucleophilicity reactivity indices . Mineva reported and discussed the reactivity descriptors of thiophene, furan, and pyrrole using Fukui indices .…”
Section: Introductionmentioning
confidence: 99%
“…A lot of work has been done in the field of theoretical chemistry in the prediction of the reactivity and definition of molecular meaningful QSAR descriptors [15,17,[46][47][48][49][50]. In particular, density functional theory (DFT) has provided formal definitions for many descriptors [33,51] and a part of them have been used as a tool to study the electrochemical redox reaction [4,[52][53][54].…”
Section: Theoretical Studiesmentioning
confidence: 99%